Peningkatan Pengetahuan pada Remaja tentang Pencegahan Pernikahan Dini di MAN Kota Tegal - Zulfiana, Evi; Harnawati, Riska Arsita; Mutiarawati, Mutiarawati; Arti, Tias Dwi; Hidayah, Seventina Nurul; Rahmanindar, Nora; Zhyakiyah, Dheffi Nanta; Fauzi, Cyrilla Azzahra Athir (Jurnal Surya Masyarakat, 2025)
Early marriage is mostly carried out by someone who is on average under 19 years old and is not ready in various aspects of marriage. This is likely to have an impact on reproductive health for both men and women. Therefore, it is necessary to prepare preparations from various aspects in carrying out marriage so that efforts to avoid the adverse impact of early marriage on reproductive health can be minimized, MAN Tegal City is a school with a large number of teenagers so it is necessary to be given increased knowledge about the prevention of early marriage. The method to prevent and overcome this problem is by Community Service Activities in the form of providing health education, the purpose of this service is to increase knowledge about the prevention of early marriage and the method carried out is to provide a pre-test before providing material to find out the knowledge of students then providing material and finally a post test.